SOCIAL ACTOR REPRESENTATIONS IN THE INTERNATIONAL CONFLICT DISCOURSE BETWEEN TRUMP AND ZELENSKY - Ariq Najmi Rihandy; Achmad Diny Hidayatullah (UIN Raden Mas Said Surakarta, 2025)
This study explores how the media construct social actor representations in the international conflict discourse between US President, Donald Trump, and Ukrainian President, Volodymyr Zelensky, during their tense meeting at the White House in February 2025. Employing Theo van Leeuwen's (2013) Social Actor Representation model within the Critical Discourse Analysis (CDA) framework, the study examines six selected news texts from Al-Ghad and BBC News Arabic. Using a qualitative approach and interactive model analysis by Miles, Huberman, and Saldana (2014), this research identifies key strategies of inclusion and exclusion used by each media outlet to position the two political figures. The findings reveal contrasting ideological patterns: Al-Ghad activates Trump as a dominant figure while marginalizing Zelensky through passivation and negative categorization; conversely, BBC News Arabic emphasizes Zelensky's agency while softening Trump’s image through passivization and nominalization. This study contributes to media discourse analysis by highlighting how ideological orientations influence the representation of global political actors and shape public perception. It also underlines the role of linguistic strategies in reproducing power relations in international conflict narratives.